ZOOPLANKTON DIVERSITY FROM FRESH WATER RESERVOIR OF MALDAD, SANGAMNER, (M.S.) INDIA - BHAGDE, RUPENDRA; KAWADE, DIPIKA; DUBE, PRIYANKA; BORGAVE, SEEMA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
The present study reveals the zooplankton diversity of fresh water reservoir from Maldad village of Sangamner Taluka, Ahmednagar district, Maharashtra. The investigations were carried out during the period of August 2019 to March 2020. Water samples were collected on the monthly basis during the morning sessions and brought to the laboratory for further analysis. The analysis of zooplankton diversity was done by using standard zooplankton identification manual. In all, eight zooplankton species from phylum Rotifera (Branchionus calyciflorus, Keratella tropica, Asplanchna brightwelli) and phylum Arthropoda; Copepoda (Mesocyclopus leukarti, Mesocyclop species, Thermocyclops hyalinus and Nauplius, a larval stage copepods), Cladocera (Cerodaphnia quadrangula) and Ostracoda (Cyclocypria kinkaidia) were recorded. This reveals presence of most of the cosmopolitan species of zooplanktons in the study area. No new species was observed during the study period. The presence of cosmopolitan species hints at low levels of pollution. However, further quantitative analysis of the same may help in analyzing the potential of the water for mankind use.